Barriers and Ethical Implications of the Ontario Ministry of Health and Long-Term Care Do Not Resuscitate Confirmation Form - Jay, Mohammad; Huynh, Jessica; Andreychuk, Sandra; Yousuf, Haroon (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
Background: Goals of care (GOC) planning involves healthcare providers (HCPs) discussing patients’ health preferences, including code status options ranging from “full code” (cardiopulmonary resuscitation [CPR] and intubation) to “do not resuscitate (DNR)”. In 2008, Ontario introduced the Do Not Resuscitate Confirmation Form (DNR-CF), which permits first responders to withhold CPR when a valid form is present. Despite routine GOC conversations during hospital admissions, few physicians complete DNR-CFs to guide community-based emergency responders. Objective: We aimed to identify the completion rates and perceived barriers to completing DNR-CFs among general internists. Methods: We conducted an online survey of general internists at two Hamilton hospitals, followed by a focus group using a semi-structured interview guide. Results: Among 14 survey respondents, only 16.7% had completed a DNR-CF, despite all being familiar with the form. Main barriers included knowledge gaps, limited accessibility and uncertainty about responsibility. Focus group participants expressed concerns about the redundancy of completing the DNR-CFs in inpatient setting, the form’s validity overtime and medicolegal implications. Conclusion: Despite widespread familiarity with DNR-CFs, completion rates remain low due to systemic, provider-related, and ethical barriers. These findings raise ethical concerns about patient autonomy and potential for unwanted harms associated with resuscitative efforts. Strategies to address these challenges include improved provider education, clearer delineation of roles, and systemic support for GOC planning. Enhancing the completion of DNR-CFs can help ensure that patient wishes are respected, particularly in community emergencies, thereby upholding ethical standards in end-of-life care.